Optimisation of Process Parameters for Preparation of Flavoured Instant Green Tea - SANKALPA K.B; Dr. Santhi Mary Mathew (Guide) (Tavanur 2017 DEPARTMENT OF FOOD AND AGRICULTURAL PROCESS ENGINEERING)
Optimization of Process Parameters for Preparation of Flavoured Instant Green Tea. doctor of philosophy
Optimization of Process Parameters for Preparation of Flavoured Instant Green Tea. doctor of philosophy